A Glimpse into Values in University Contexts: Cuba - Reyes-Quiñones, Edelmis Cristina (2021)
The values in the university context, is intentionally prioritized in all social spaces, therefore the credibility and relevance of the university of the XXI century will be evident to the extent that professionals are forged that are men and women of peace and propriety, whose solid humanistic formation and high scientific-technical training are a source of inspiration to undertake with responsible audacity, the search for solutions to save the planet and build a better world for all.